Enacting evidence-based practice: pathways for community nurses. (2nd August 2019) - Teodorowski, Piotr; Cable, Clare; Kilburn, Sally; Kennedy, Catriona
Abstract : Community nurses are expected to deliver evidence-based practice, which is challenging given the diversity and breadth of the evidence base from which they can draw. This study aimed to explore community nurses' experiences of implementing change in their practice. Qualitative semi-structured interviews (n=9) and focus groups (n=2) with community nurses (n=17) were conducted. Three pathways to introduce change in practice were identified by participants: bottom-up, top-down and collaborative pathways. These are based on the nature of the proposed change, the available evidence, 'buy in' from colleagues and issues around implementation. The findings identify approaches to implementing change in community nursing practice. Practitioners would benefit from support to navigate the complex process of change through managerial support, ongoing education, accessible online resources and support through a practice development role.